Activity pattern of Anas georgica assessed by camera trap in a temporary wetland in Chile. - Chávez Villavicencio, César Lautaro (2022)
Camera traps allow us to estimate abundance, distribution, habitat use and activity patterns of fauna. It has rarely been used in the study of birds and can be a good option when direct or satellite observation methods are limited. The idea was to test the effectiveness of camera traps, on a small scale, in the study of waterfowl activity patterns, compared to point observation methods. Anas georgica was used as the object of study with the objective of determining their activity patterns in spring-summer and autumn-winter. A camera trap was installed in a temporary wetland active 24 hours a day for one year. Activities were recorded in six time periods: sunrise, morning, afternoon, twilight, night and early morning. The activity pattern was analyzed with the density function (kernel method). In spring-summer, 96 records were obtained. The afternoon period presented a predominance of activity records while in the twilight there were no activity records. The autumn-winter season had 70 records. There was no evidence of a predominance of activities in any of the periods. The most recorded activity was swimming (spring-summer and autumn-winter). Spring-summer presented greater activity between 12:00 and 18:00 hours, while nocturnal activity was lower. In autumn-winter, activity was highest between 9:00 a.m. and 12:00 noon. This work proves that a camera trap works the same as a point observer with the advantage of 24-hour operation.